The Role of Language Learning Strategies in Developing Intercultural Communication Skills: A Qualitative Case Study of EFL Students - Jihad, Adriani; Dollah, Syarifuddin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
The interconnected world of the 21st century has shifted the goal of English as a Foreign Language (EFL) education from mere linguistic competence to the holistic development of Intercultural Communication Competence (ICC). This study investigates the crucial role of Language Learning Strategies (LLS) employed by EFL students in facilitating the acquisition and deployment of ICC. Employing a qualitative case study design, the research explores the lived experiences of five purposively selected EFL university students in Indonesia, focusing on their strategic actions when engaging in cross-cultural interactions. Data were collected through semi-structured interviews, reflective journals, and non-participant observation of simulated intercultural tasks. The findings reveal that social/affective LLS (e.g., seeking out native speakers, showing empathy) and specific metacognitive LLS (e.g., directed attention to cultural norms, self-monitoring for cultural appropriateness) are the most instrumental in developing ICC's key components: Attitudes (openness and curiosity), Knowledge (understanding cultural values), and Skills (interpreting and relating). The study concludes that explicit instruction in LLS, particularly those encouraging social and reflective engagement, is vital for transforming EFL learners into intercultural competent global citizens. This work provides pedagogical implications for EFL educators to integrate LLS training within a culturally-rich curriculum. Keywords: Language Learning Strategies (LLS), Intercultural Communication Competence (ICC), EFL Students, Qualitative Case Study, Intercultural Awareness, Social Strategies.